1984
DOI: 10.1007/bf00151322
|View full text |Cite
|
Sign up to set email alerts
|

Energy release in solar flares

Abstract: We examine observational evidence concerning energy release in solar flares. We propose that different processes may be operative on four different time scales: (a) on the sub-second time scale of 'sub-bursts' which are a prominent feature of mm-wave microwave records; (b) on the few-seconds time scale of 'elementary bursts' which are a prominent feature of hard X-ray records; (c) on the few-minutes time scale of the impulsive phase; and (d) on the tens-of-minutes or longer time scale of the gradual phase.We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 33 publications
3
55
1
1
Order By: Relevance
“…This is probably an upper limit to the thickness of the CS, and what is appropriate at later times cannot be easily predicted: while h increases, M A decreases, and these processes compete in determining the actual size. These values are much larger than those obtained by assuming that the reconnecting region has the typical size of elementary flux tubes (see, e.g., Sturrock et al 1984), and they show that the CS characteristics are still far from being identified.…”
Section: Introductioncontrasting
confidence: 56%
“…This is probably an upper limit to the thickness of the CS, and what is appropriate at later times cannot be easily predicted: while h increases, M A decreases, and these processes compete in determining the actual size. These values are much larger than those obtained by assuming that the reconnecting region has the typical size of elementary flux tubes (see, e.g., Sturrock et al 1984), and they show that the CS characteristics are still far from being identified.…”
Section: Introductioncontrasting
confidence: 56%
“…Models of colliding and reconnecting magnetic flux tubes have been developed both for two ribbon flares and compact flares (e.g. Sturrock et al 1984;Jakimiec et al 1998). In these models the increase of twisting of the magnetic flux tubes in the corona accumulates free magnetic energy, which is released when the flux tubes are brought into contact.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least three timescale on which acceleration processes operate. An overview which incorporates these timescales was suggested by Sturrock et al [33], who however considered only the high-frequency spikes in discussing the shortest timescale. With minor modifications their overview is as follows.…”
Section: -4 Timescales In Accelerationmentioning
confidence: 99%